Pengelolaan Aset Wakaf di Indonesia - Triani Arofah; Ratu Ayu Sri Wulandari; Gista Rismayani (Jurnal Riset Akuntansi Soedirman, 2025)
This study examines waqf asset management in Indonesia by synthesizing existing literature from governance, accountability, and implementation perspectives. The purpose of this study is to identify the dominant institutional factors that explain the persistent gap between the normative potential of waqf and its practical performance. Using a structured literature review approach, this study analyzes 107 Scopus-indexed journal articles relevant to waqf governance, accounting-based accountability, and institutional capacity. The findings indicate that ineffective waqf asset management is primarily driven by fragmented governance structures, weak accountability mechanisms—particularly in accounting and reporting practices—and limited implementation capacity within waqf institutions. These three dimensions are interrelated and jointly determine the effectiveness and sustainability of waqf asset management, rather than operating as isolated factors. The study contributes to the literature by offering an integrative conceptual framework that links governance and accountability with implementation capacity as a mediating institutional condition. Practically, the findings provide evidence-based insights for policymakers and waqf practitioners to strengthen governance arrangements, improve accounting-based accountability, and enhance institutional capacity to support more effective and sustainable waqf asset management in Indonesia.